2019
DOI: 10.1017/s0266467419000312
|View full text |Cite
|
Sign up to set email alerts
|

The landscape-scale drivers of herbivore assemblage distribution on the central basalt plains of Kruger National Park

Abstract: The distribution and abundance of herbivores in African savannas are constrained by interactions between abiotic and biotic factors. At the species-level, herbivores face trade-offs among foraging requirements, vegetation structure and the availability of surface water that change over spatial and temporal scales. Characterizing herbivore requirements is necessary for the management of the environment in which they occur, as conservation management interventions such as fencing and artificial water provision c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…We found that when freed from the constraints of decreased forage quality and quantity, and limited water availability in the dry season, the probability of presence by species at their preferred forage resource increased. This highlights the trade-off species face under the constraints of the dry season, and species-specific traits which they have adapted to meet metabolic requirements when resources are not readily available (also observed at the landscape-scale, see Young et al (2019)). Overall, selectivity in larger-bodied species was harder to unravel either due to low camera detection across the sampling period, or their selectivity being at scales greater than what we tested.…”
Section: Discussionmentioning
confidence: 87%
“…We found that when freed from the constraints of decreased forage quality and quantity, and limited water availability in the dry season, the probability of presence by species at their preferred forage resource increased. This highlights the trade-off species face under the constraints of the dry season, and species-specific traits which they have adapted to meet metabolic requirements when resources are not readily available (also observed at the landscape-scale, see Young et al (2019)). Overall, selectivity in larger-bodied species was harder to unravel either due to low camera detection across the sampling period, or their selectivity being at scales greater than what we tested.…”
Section: Discussionmentioning
confidence: 87%
“…Each model was inspected for the correct distribution of residuals using the quantile-quantile TA B L E 1 The number of independent camera trap triggers for each species, during the four austral seasons, on Korannaberg (K) and Lekgaba (L). (QQ) plots and, where necessary, heat load data was square root transformed to improve model fit (Glover-Kapfer et al, 2019;Suraci et al, 2016;Young et al, 2020). When the analysis was done on square root-transformed data, it has been indicated in the results of the GLM (Appendix S2); however all figures depict the actual heat loads measured by the miniglobes.…”
Section: Discussionmentioning
confidence: 99%
“…Site (Korannaberg, lions absent and Lekgaba, lions present), season (autumn, winter, spring, and summer), and their interaction were the predictor variables, with coefficients estimating differences in heat loads corresponding to times of activity. Each model was inspected for the correct distribution of residuals using the quantile‐quantile (QQ) plots and, where necessary, heat load data was square root transformed to improve model fit (Glover‐Kapfer et al., 2019; Suraci et al., 2016; Young et al., 2020). When the analysis was done on square root‐transformed data, it has been indicated in the results of the GLM (Appendix S2); however all figures depict the actual heat loads measured by the miniglobes.…”
Section: Methodsmentioning
confidence: 99%
“…Megafauna populations are affected by natural biotic and abiotic processes 13 , including forage quality and quantity, fire, water availability, disease, and predation [14][15][16][17][18][19][20][21] . These processes can regulate megafauna populations and influence their distribution within the broader landscape 22,23 . Megafauna, in turn, can have a significant impact on vegetation structure, composition 24 , and ecosystem processes and functioning, such as foraging, trampling, and nutrient/seed dispersal 25,26 .…”
Section: Natural Vs Human Driversmentioning
confidence: 99%